2021
DOI: 10.3389/fphar.2021.629513
|View full text |Cite
|
Sign up to set email alerts
|

Xiao-Yin-Fang Therapy Alleviates Psoriasis-like Skin Inflammation Through Suppressing γδT17 Cell Polarization

Abstract: Psoriasis is an immune-mediated chronic inflammatory skin disease primarily mediated by the activation of interleukin (IL)-17-producing T cells. Traditional Chinese Medicine (TCM) represents one of the most effective complementary and alternative medicine (CAM) agents for psoriasis, which provides treasured sources for the development of anti-psoriasis medications. Xiao-Yin-Fang (XYF) is an empirically developed TCM formula that has been used to treat psoriasis patients in Shanghai Changhai Hospital for over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Except for the untreated control group (CON), mice in other groups were administered topically at a daily dose of 62.5 mg of a cream preparation containing 5% IMQ on the shaved back (2 × 3 cm) of each mouse to induce the psoriasis model. Mice in the positive control group were administered intragastrically with 40 mg/kg/d TWP tablets (TWP, a patented Chinese drug widely used for the clinical treatment of psoriasis in China) (Wu et al, 2015; Zhang et al, 2021; Zhao et al, 2016). The oral dose of HQG was determined according to a previous clinical observation study (Chin J Dermatovenereol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for the untreated control group (CON), mice in other groups were administered topically at a daily dose of 62.5 mg of a cream preparation containing 5% IMQ on the shaved back (2 × 3 cm) of each mouse to induce the psoriasis model. Mice in the positive control group were administered intragastrically with 40 mg/kg/d TWP tablets (TWP, a patented Chinese drug widely used for the clinical treatment of psoriasis in China) (Wu et al, 2015; Zhang et al, 2021; Zhao et al, 2016). The oral dose of HQG was determined according to a previous clinical observation study (Chin J Dermatovenereol.…”
Section: Methodsmentioning
confidence: 99%
“…Scutellaria baicalensis is a commonly used herbal medicine in traditional Chinese medicine, which has been found in the prescriptions for the treatment of PSO such as Xiao‐Yin‐Fang (Zhang et al, 2021). Chemical studies have shown that flavonoids and their glycosides are the main effective substance of Scutellaria baicalensis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because human cells have no cell wall structure, this antibacterial therapy does less damage to human cells. Because EM has broad-spectrum effects, including anti-inflammatory, antioxidant, and antibacterial effects ( 42 ), we used a confocal probe and flow cytometry to detect whether M-LFLIU could enhance the antibacterial effect of EM-stimulated ROS. In the process of the body’s fight against bacteria, proper ROS promotes the body’s immunity and repair.…”
Section: Discussionmentioning
confidence: 99%
“…In modern pharmacology, S. flavescens has been found to be beneficial for treating inflammatory disorders such as eczema, colpitis, ulcerative colitis, and psoriasis (Ma et al, 2018). Some complex formulas containing S. flavescens have been proven to alleviate inflammatory skin diseases, including contact dermatitis, alopecia, and psoriasis (H. W. Kim et al, 2012; Takahashi et al, 2016; X. Zhang et al, 2021). Phytochemical assays identified that S. flavescens contains abundant flavonoids, quinolizidine alkaloids, and triterpenoids (Dong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%